Supplemental Microalgal DHA and Astaxanthin Affect Astaxanthin Metabolism and Redox Status of Juvenile Rainbow Trout - Kun Wu; Beth M. Cleveland; Mark Portman; Wendy M. Sealey; Xin Gen Lei (MDPI AG, 2020)
Microalgal docosahexaenoic acid (DHA) and astaxanthin (AST) may substitute for fish oil and synthetic AST in aquafeeds. This study explored the effects and mechanisms of those substitutions on AST metabolism and redox status of rainbow trout fed plant protein meal (PM)- or fishmeal (FM)-based diets. Two parallel experiments (PM vs. FM) were performed with 612 juvenile rainbow trout for 16 weeks as a 2 × 3 factorial arrangement of treatments with two AST sources (synthetic (SA) vs. microalgal (AA), at 80 mg/kg) and three levels (0, 50, and 100%) of fish oil substitutions with DHA-rich microalgae. The fish oil substitutions exhibit main effects (p < 0.05) and/or interactive effects (p < 0.05) with the source of AST on AST deposition, malondialdehyde and glutathione concentrations, and mRNA levels and activities of major redox enzymes (glutathione reductase (GR), glutathione peroxidase (GPX), glutathione S-transferase (GST), and superoxide dismutase (SOD)) in the muscle and liver of trout fed both diet series. The AST source produced only differences in tissue AST deposition (p < 0.05) and number of metabolites. In conclusion, the substitutions of fish oil by the DHA-rich microalgae exerted more impacts than those of SA by AA on redox status and functional expression of antioxidant enzymes in the tissues of rainbow trout.